O ciclo básico nas universidades do estado do Paraná visão critica e proposta de reestruturação - César, Zénite Terezinha Ribas (Semina: Ciências Agrárias, 1983)
The objectives of this present work are to evaluate to what point the Basic Curriculum of the State Universities of Parana exercise the functions that were conferred by the legislature, and do these functions correspond to the expectation of society. Hopefully, these conclusions will contribute toward the university community being able to take a position which addresses important aspects of University reform. The research is composed of some preliminary considerations, a theorectical treatment of the problem, formulation of a conceptual framework, resulting methodology, analysis of the different problems encountered, a proposal for restructuring, and conclusions. The restructuring proposal consists of five parts referent to the functions and objetives, structure and function, content, methodology, and strategies fo follow up and evaluation. Among the outstanding conclusions are the following: 1) - The Basic Curriculum was not an idea assumed by the State Universities of Parana, but an innovation imposed by the legislation and did not involve the university community. 2) — The professors in general are preoccupied with teaching their subject and riot with any philosophy of teaching, philosophy of science, or even with how their subject fits into the general pattern of the student's education. 3) - Teaching reforms should not be limied to the simple substitution of one subject for another. Deeper thought needs to be given to arrive at a general agreement. No reform is worthwhile unless the community is convinced that its bases has validity.